Os efeitos do gamification na avaliação de linguagem inglesa no ensino superior. - Serra, Roseli Wanderley de Araújo (2020)
This research aims at analyzing the effects of Gamification in the assessment for the teaching and the learning of English as a Foreign Language (EFL) in Higher Education (HE), specifically, describing and explaining the effects of this Gamified Assessment for teaching and learning the English Language. Gamification means using elements of the game in non-game contexts (DETERDING et al., 2011). We propose to: identify web Apps (internet sites that behave like applications), which are accessed through a browser and have responsive behavior and applications in Mobile Digital Technology which enable the use of Gamification as a support tool the teaching-learning of EFL; observe the pedagogical activities they contain and, through the choice of some of those web Apps and applications, describe the effects for the teaching and learning of EFL through a Gamified Assessment, with the purpose of generating motivation, engagement and satisfaction to teachers and to language learners. Our research has as theoretical support: theories on Evaluation; Digital literacies; Pedagogy of Multiliteracies; Architectonics in the Bakhtinian perspective, Information and Communication Technologies (ICT), Multimodality, and Semiotics. Methodologically, it is a quantitative and qualitative and descriptive research, of the case study type. According to Yin (2010), the case study is one of the strategic and challenging ways of doing research and allows an investigation to preserve the holistic and significant characteristics of real-life events. The participants of the research were: two graduating students from the sixth semester of the School of Language and Literature - Portuguese and English, from a Higher Education institution in the city of Recife, an English teacher from the School of Language and Literature course at that institution and ten English teachers who responded to the semi-structured interview in the digital medium. For that, we established the following strategies: (i) observations of sixth period LI classes; (ii) semi-structured interviews with the two students and LI teachers; (iii) construction of the Gamified Assessment from the perspective of the game's architecture; (iv) application of Gamified Evaluation in TDM; (v) application of a new semi-structured interview with the students after the results. Therefore, on-screen research is a means of expanding and exploring models to evaluate through Gamification. The results of our research attested to the positive effects of Gamification and Gamified Assessment in LI in ES, making the teaching and learning of the English language more autonomous, interactive, multimodal, challenging, effective, pleasurable, engaging and which fosters in the student the necessary motivation for progress in the learning process, from the reflection on the English language, as a foreign language in a game process in non-game environments.